Agroforestry for NTFPs Conservation and Economic Upliftment of Farmers - Sulaiman Quli, S. M. (Indian Forester, 2001)
The main objective of the present communication is not limited only up to the publicity and extension of agroforestry as a multipurpose beneficial technique , rather it is an attempt to illuminate the new dimension of Agroforestry , through which the effective conservation of NTFPs can be achieved with simultaneous economic improvement of the farmers. The paper highlights the alarming level of the loss of forest cover. Keeping in view the potentials of the agroforestry , appropriate schemes have been formulated to conserve the NTFP resources along with simultaneous improvement of the economic conditions of the farmers. For the effective motivation of farmers to ensure the large-scale adoption of the proposed agroforestry schemes , the economic potentials of the agroforestry have been illustrated. It is expected that proper implementation of the proposed schemes can help in conservation of the NTFP resources with simultaneous economic improvement of the farmers.